Encyclopedia of women in the American West - Bakken, Gordon Morris; Farrington, Brenda (Sage, 2003)
The Encyclopedia of women in the American West captures the lives of more than 150 women who made their mark from the mid-1800s to the present, contextualizing their experiences and contributions to American society. Including many women biographied for the first time, the Encyclopedia offers immense value and interest to practicing historians as well as students and the lay public. The West is often portrayed as a rough and tumble man's world, but behind these men--and often independently--were women with the dreams, strength, and determination to make a difference. The Encyclopedia of women in the American West is a tribute to their independence, intelligence, courage, spirit, perseverance, and daring.